Fault Classification and Location in Three-Phase Transmission Lines Using Wavelet-based Machine Learning - Zerahny C.K.Y.; Yun L.K.; Raymond W.J.K.; Mei K.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Discrete wavelet transforms; Electric fault location; Electric lines; Machine learning; Neural networks; Wavelet decomposition; Fault classification; Fault estimation; Fault zone; Long transmission lines; Machine learning models; Phase transmission; Three phase; Three phasis; Transmission-line; Two phase; Location